On the population model with a sine function - Bula, I.; Vintere, A. (Mathematical Modelling and Analysis, 2006)
In the interval [0,1] function sr(x) = r sin πx behaves similar to logistic function h μ (x) = μx(1‐ x). We prove that for every r > there exists subset ? ⊂ [0,1] such that sr : ? → ? is a chaotic function. Since the logistic function is chaotic in another subset of [0,1] but both functions have similar graphs in [0,1] we conclude that it can lead to errors in practice. First Published Online: 14 Oct 2010